Why Do Tetrapropylammonium Chloride and Sulphate Salts Destabilize the Native State of Globular Proteins? - Giuseppe Graziano (The Scientific World Journal)
It has recently been shown that aqueous solutions of tetrapropylammonium chloride and sulphate salts destabilize the folded conformation of Trp-peptides (Dempsey et al., 2011). This result is rationalized by the application of a statistical thermodynamic approach (Graziano, 2010). It is shown that the magnitude of the solvent-excluded volume effect, the main contribution for the native state stability, decreases in both aqueous 2 M TPACl solution and aqueous 1 M TPA2SO4 solution. This happens because TPA+ ions are so large in size and interact so weakly with water molecules, due to their very low charge density, to be able to counteract the electrostrictive effect of chloride and sulphate ions on the water structure, so that the density of their aqueous solutions is smaller or only slightly larger than that of water.